Different components of air pollutants and neurological disorders - Fu, Chunlia; Kuang, Daibing; Zhang, He; Ren, Jinxin; Chen, Jialong (Frontiers in Public Health, 2022)
The harmful effects of air pollution can cause various diseases. Most research on the hazards of air pollution focuses on lung and cardiovascular diseases. In contrast, the impact of air pollution on neurological disorders is not widely recognized. Air pollution can cause various neurological conditions and diseases, such as neural inflammation, neurodegeneration, and cerebrovascular barrier disorder; however, the mechanisms underlying the neurological diseases induced by various components of air pollutants remain unclear. The present paper summarizes the effects of different components of air pollutants, including particulate matter, ozone, sulfur oxides, carbon oxides, nitrogen oxides, and heavy metals, on the nervous system and describes the impact of various air pollutants on neurological disorders, providing ideas for follow-up research.